Moringa oleifera leaves protein suppresses T-lymphoblastic leukemogenesis via MAPK/AKT signaling modulation of apoptotic activation and autophagic flux regulation - Liu, Xiaoxue; Yang, Hao; Xie, Shanna; Wang, Xinyu; Tian, Yang; Song, Shuang (Frontiers in Immunology, 2025)
Acute lymphoblastic leukemia (T-ALL) is one of the most common hematologic malignancies in children worldwide. Despite advances in chemotherapy in recent years, more than 50% of adult T-ALL patients still experience treatment resistance and relapse/refractory disease. Moringa oleifera, a new food resource in China, has high nutritional value and various pharmacological activities. Moringa oleifera protein is one of the main active ingredients in Moringa oleifera leaves, and some studies have shown that Moringa oleifera protein has antioxidant, anti-inflammatory, antibacterial, anticancer, and other bioactivities; however, the anti-acute lymphoblastic leukemia (T-ALL) activity of the Moringa oleifera protein and its mechanism of action are still unclear. In this study, we used Moringa oleifera leaves protein as the experimental material and used the MTT assay, flow cytometry, and Western blot techniques to study the effects of Moringa oleifera leaves protein on Jurkat cell growth, apoptosis, and the cell cycle in vitro and the underlying molecular mechanism. Moringa oleifera leaves protein inhibited Jurkat cell proliferation; induced apoptosis and cycle arrest; increased autophagy; and inhibited Jurkat cell proliferation by regulating the MAPK/AKT pathway. The results of this study provide new ideas and a theoretical basis for the development of Moringa oleifera leaves protein for the prevention and treatment of leukemia.